Advanced performance simulation of gas turbine components and fluid thermodynamic properties - Sethi, Vishal (Cranfield University, 2008)
The VIVACE European Cycle Program (“VIVACE-ECP”) was part of the virtual engine sub-project of VIVACE and was worth 6.63 million Euros. The main outcome of the “VIVACE-ECP” was the development of a cost effective gas turbine simulation environment called PROOSIS. PROOSIS, which is the Greek word for “propulsion”, is an acronym for “PRopulsion Object Oriented SImulation Software”. PROOSIS was developed by facilitating optimal use of multi-partner gas turbine performance simulation research and development resources and expertise. PROOSIS is a single framework which provides shared standards and methodologies for the European Union (EU) gas turbine community, including original equipment manufacturers (OEMs), industrial companies, universities and research centres. The primary objective of this doctoral thesis is to present advanced performance simulation models of gas turbine components and advanced fluid modelling capabilities developed by the author for the PROOSIS standard components library (SCLib). The main aims of this research are to provide a detailed insight into the effects of dissociation on fluid thermodynamic properties and subsequently on gas turbine performance. Detailed descriptions of the development of an advanced fluid model and a robust flow continuity model, which are the foundation of the PROOSIS standard component library, are provided. The effects of dissociation on isolated Burner and Afterburner components as well as overall engine performance are discussed with the aid of several case studies. Additionally, advanced performance simulation models of Burner and Afterburner components are presented. The development of an extended parametric representation of compressor characteristics is also analysed. Several advanced capabilities of PROOSIS (including test analysis, customer deck generation, 3D compressor zooming and distributed computing) are also introduced. The “evolution of PROOSIS” is presented with an in-depth analysis of the collaborative structure and project management of the VIVACE- ECP, as well as the channels of communication, technology transfer and quality control. A clear emphasis is placed on the contribution of the author to each of these tasks and subsequently the “VIVACE-ECP” as a whole. The main outcome of this work is the development of an advanced fluid model which comprises multi-dimensional fluid property tables for several fuels. The advanced fluid model also caters for “levels of dissociation” ranging from “no dissociation” to chemical equilibrium. This advanced fluid model is complimented by a robust flow continuity model, also developed by the author, which calculates the unknown local flow properties at any point in an engine model. These robust, advanced fluid and flow continuity models facilitate improved accuracy thereby providing a solid foundation for several advanced gas turbine performance simulation capabilities.